O conhecimento musical no cotidiano dos professores unidocentes - Lírio, Eliane de Castilho (2010)
This dissertation submits a qualitative research performed in a public school's middle school and approaches building up the pedagogue's musical knowledge and the implications of musical culture in the first years of middle school. The research splits up in tree chapters, of which two are dedicated on debating about how to acquire knowledge and the contributions from various areas of knowledge that can supply subsidies in interdisciplinarity for a specific theory of construction of knowledge in musical terms. Even though considering music as a knowledge that has it's own articulated, intermediated contents in culture. The third chapter will bring musical concepts and the musical experiences from teachers that have participated in this research and how their different life experiences were achieved by interviews and written narratives that idnetifies this school sphere. In this interaction, judgement values, building up musical know-how and the usage of music in everyday scholarship are present. The results achieved by occasion in field research are analyzed by bibliographical research.